Branded app implementation at the London Symphony Orchestra. (3rd May 2016) - Gosling, Victoria; Crawford, Garry; Bagnall, Gaynor; Light, Ben
Abstract : Purpose: – The purpose of this paper is to consider the key findings of a yearlong collaborative research project focusing on the London Symphony Orchestra's development, implementation and testing of a branded smartphone app. This app was designed to primarily sell discounted tickets, engage and inform a student audience. Design/methodology/approach: – A mixed-method approach including an analysis of the technology, focus groups and interviews was used. Findings: – Though the aims of app developers and marketers are often to provide customers with more choice and interactivity, this research suggests that though the app proved a useful mechanism for selling discounted tickets, it indicates that existing customers were mostly enroled and mobilised via a limited and focused functionality for the app. Originality/value: – This paper is significant as mobile phone use remains comparatively under-researched, in particular there is still a relatively small literature on the growing phenomena of apps, and even less on their use in brand marketing. Also importantly, though this paper offers a consideration of one case, the app has since been expanded to include the ticketing for ten major orchestras in London, and moreover, many of the lessons learnt from this study will be of relevance to other arts organisations.